FACTORS DRIVING CREATIVITY AND FUTURE DIRECTIONS FOR ECONOMIC EMPOWERMENT - Njenga Gitahi, Samson (kabarak university, 2016)
tivity is an indispensable development over the long period approach problems and solutions existing ideas together in new combinations the need for efficiency, economy, evaluation ethics and market concerns global economy, Johnson and institutions must find ways for competences as the old advantage quickly eroded owing to dynamics Because of the fact that changes public sector, every institution environment otherwise, they would
Keywords: FACTORS DRIVING CREATIVITY; FUTURE DIRECTIONS FOR ECONOMIC EMPOWERMENT